A newborn of mother with thyroid disease - Fabian-Danielewska, Anna; Żukowska, Magdalena; Korabiusz, Katarzyna; Petriczko, Elżbieta (Journal of Education, Health and Sport, 2018)
Thyroid diseases are frequent endocrinopathies during childbearing, affecting about 5-20% of pregnant women. They can appear in women both before and during pregnancy. The most common form of thyroid disease is hypothyroidism, mainly Hashimoto's disease. Hyperthyroidism is less frequent, but the most common form is Graves' disease. Disorders of thyroid function in the newborn cause permanent consequences mainly in the development of the nervous system. Therefore, it is very important to properly diagnose and quickly apply treatment when a disorder is detected. In Poland there is a screening program for newborns detecting congenital hypothyroidism. In this program the TSH level is measured in second or third day of life. Diagnosis of hyperthyroidism in children of mothers with Graves' disease consists of examining the levels of TRAb antibodies in the mother especially in the third trimester, and in the umbilical cord blood or blood of the newborn. It should also be observed if symptoms of fetal hyperthyroidism are present. Treatment of both hypothyroidism and hyperthyroidism should be started without undue delay. Both of these neonatal endocrinopathies are mostly transient and retreat with the elimination of antibodies, i.e. within 1-6 months. Therefore, it is necessary to verify the diagnosis and the need of further treatment after this time.